Immune-Related Adverse Events (irAEs) in Cancer, with Inputs from a Nursing Expert: A Review - Buch, Sajad Ahmad; Baba, Mudasir Rashid (Indian Journal of Medical and Paediatric Oncology, 2022)
Immune checkpoint inhibitors (ICPis) belong to a group of immunotherapeutic agents that act on different immune cells and tumor cells and reactivate the suppressed immune system of the host. The emergence of immunotherapy has resulted in the successful management of many malignancies. High success rates with certain advanced cancers have attributed wide importance and relevance to the use of immunotherapy. Although ICPis have gained huge popularity, their use often leads to side effects that can affect almost any system; immune-related adverse events (irAEs). These adverse events occur due to unrestrained T cell activity that unsettles the immune homeostasis of the host. Although close monitoring for toxicities controls the events on most of the occasions, the inability to diagnose them early may prove fatal on some occasions due to their subtle and nonspecific symptoms. This review summarizes in brief the usual irAEs and their management, besides a very important nursing perspective, from a nursing expert about an overall insight into the routine irAEs.
Keywords: immune-related adverse events; immune checkpoint inhibitors; immunosuppressant; cytotoxic T lymphocyte antigen 4; programmed cell death protein 1